Nonunique and nonuniform mapping in few-body Coulomb-explosion imaging - Sayler, A. M.; Eckner, E.; McKenna, J.; Esry, B. D.; Carnes, K. D.; Ben-Itzhak, I.; Paulus, G. G. (My University, 2018)
Much of our knowledge of molecular geometry and interaction dynamics comes from indirect measurements of the molecular fragments following breakup. This technique—Coulomb-explosion imaging (CEI), i.e., determining the initial molecular configuration of a system from the momenta of the resulting fragments using knowledge of the particle interactions—is one of the fundamental tools of molecular physics. Moreover, CEI has been a staple of molecular studies for decades. Here we show that one often cannot assign a unique initial configuration to the few-body breakup of a polyatomic molecule given the measurement of the resulting fragments' momenta. Specifically, multiple initial configurations can result in identical momenta for a molecule breaking into three or more parts. Further, the nonunique and nonuniform mapping from the initial configuration to the measured momenta also significantly complicates the determination of molecular alignment at the time of breakup.
Citation: Sayler, A. M., Eckner, E., McKenna, J., Esry, B. D., Carnes, K. D., Ben-Itzhak, I., & Paulus, G. G. (2018). Nonunique and nonuniform mapping in few-body Coulomb-explosion imaging. Physical Review A, 97(3), 033412. https://doi.org/10.1103/PhysRevA.97.033412